Electrochemical and biological response of titanium (cp-Ti) after silicon ion implantation. Issue 1 (9th October 2019) - Deen, K.M.; Farooq, A.; Rizwan, M.; Ahmad, A.; Haider, W.
Abstract : Purpose: This study/paper aims to the authors applied low "Si" ions dose over cp-Ti-2, and the potent dose level was optimized for adequate corrosion resistance and effective proliferation of stem cells. Design/methodology/approach: The cp-Ti surface was modified by silicon (Si) ions beam at 0.5 MeV in a Pelletron accelerator. Three different ion doses were applied to the polished samples, and the surface was characterized by XRD and AFM analysis. Findings: At moderate "Si" ion dose (6.54 × 10 12 ions-cm −2 ), the potential shifted to a noble value. The small "icorr " (1.22 µA.cm −2 ) and relatively large charge transfer resistance (43.548 kΩ-cm 2 ) in the ringer's lactate solution was confirmed through Potentiodynamic polarization and impedance spectroscopy analysis. Compared to cp-Ti and other doses, this dose level also provided the effective proliferation of mesenchymal stem cells. Originality/value: The dosage levels used were different to previous work and provided the effective proliferation of mesenchymal stem cells.